THE PRINCIPAL'S CONTRIBUTION IN IMPROVING THE QUALITY OF ISLAMIC RELIGIOUS EDUCATION LEARNING AT ELEMENTARY SCHOOL 05 PASAMAN - Maysarah, Siti; Annisa Humaira, Vinni; Salman (Amanah Publishing, 2024)
This research is motivated by the principal's constant effort to improve the quality of Islamic religious education by observing the development of Islamic religious teachers in teaching, student morality, and achievement in Islamic religious education. The objectives of this study are: 1) To determine the quality of Islamic religious education at Elementary School 05 Pasaman, 2) To determine the principal's contribution to improving the quality of Islamic religious education at Elementary School 05 Pasaman. This study is a field research study. The key informants in this study were the Islamic religious education teacher and the principal, while the supporting informants were students. The data collection techniques used in this study were interviews, observation, and documentation. Based on the results of this study, it can be concluded that 1) The quality of Islamic religious education and learning at Elementary School 05 Pasaman has increased, this is indicated by the frequent students winning championships in various religious competitions, 2) The principal's contribution in improving the quality of Islamic religious education and learning at Elementary School 05 Pasaman includes: a) preparing activity plans, b) building a solid work team, c) improving teacher competence, d) building relationships with parents and the community, e) providing adequate facilities and infrastructure, f) adjusting teaching objectives to the curriculum, g) ensuring the content of special materials, h) using criteria and standardization.